2012
DOI: 10.2174/138920012798356952
|View full text |Cite
|
Sign up to set email alerts
|

Design of Curcumin loaded Cellulose Nanoparticles for Prostate Cancer

Abstract: Prostate cancer (PC) is the most frequently diagnosed disease in men in the United States. Curcumin (CUR), a natural polyphenol, has shown potent anti-cancer efficacy in various types of cancers. However, suboptimal pharmacokinetics and poor bioavailability limit its effective use in cancer therapeutics. Several successful CUR nanoformulations have recently been reported which improve upon these features; however there is no personalized safe nanoformulation for prostate cancer. This study contributes two impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 52 publications
3
65
0
Order By: Relevance
“…Recently, various nano formulations of curcumin have been synthesized to overcome these issues. Nanoparticle-loaded curcumin appeared to achieve high permeability, good bioactivity and low metabolism in animal models [25-27]. In the present study, the nanomaterial distearoylphosphatidyethanolamin-polyethylene glycol (DSPE-PEG) was employed as a nanocarrier for curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, various nano formulations of curcumin have been synthesized to overcome these issues. Nanoparticle-loaded curcumin appeared to achieve high permeability, good bioactivity and low metabolism in animal models [25-27]. In the present study, the nanomaterial distearoylphosphatidyethanolamin-polyethylene glycol (DSPE-PEG) was employed as a nanocarrier for curcumin.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin nanoformulations ( Figure 1B) were obtained following our previous protocols using PLGA, β-cyclodextrin, cellulose, nanogel (polyNIPAM), and dendrimer through self-assembly/ complexation/redox free radical solution polymerization or encapsulation techniques. 21,22,26,36 For consistency, all curcumin nanoformulations were processed with 20 wt% curcumin loading. A schematic representation of curcumin nanoformulations are provided in Figure 1B.…”
Section: Methodsmentioning
confidence: 99%
“…16,[23][24][25] In our previous study, we describe a comparative evaluation of β-cyclodextrin, hydroxyl propyl methyl cellulose (cellulose), polylactic-co-glycolic acid (PLGA) and dendrimer curcumin nanoformulations with free curcumin using cytotoxicity, cellular uptake, and apoptosis studies in cancer cells and suggests a close relationship with the therapeutic efficacy of the formulation. 26 However, there is no tool to evaluate the behavior of curcumin nanoformulations in vivo. Similarly, while a number of curcumin nanoformulations have been reported in the literature, so far there has been no comparative study to evaluate which formulation(s) is more efficient for in vivo cancer therapeutics.…”
Section: Introductionmentioning
confidence: 99%
“…It was found that HPMA-based polymeric micelles 41 significantly enhanced the solubility of CM. The PEG-HPMA-Bz micelles showed the best solubilization 42 properties. CM loaded polymeric micelles showed sustained release of the loading CM for more than 43 20 days.…”
mentioning
confidence: 98%